Improved 25-level inverter topology with reduced part count for PV grid-tie applications - Radouane Majdoul; Abelwahed Touati; Abderrahmane Ouchatti; Abderrahim Taouni; Elhassane Abdelmounim (Institute of Advanced Engineering and Science, 2021)
A new bidirectional multilevel inverter topology with a high number of voltage levels with a very reduced number of power components is proposed in this paper. Only TEN power switches and four asymmetric DC voltage sources are used to generate 25 voltage levels in this new topology. The proposed multilevel converter is more suitable for e-mobility and photovoltaic applications where the overall energy source can be composed of a few units/associations of several basic source modules. Several benefits are provided by this new topology: Highly sinusoidal current and voltage waveforms, low Total Harmonic Distortion, very low switching losses, and minimum cost and size of the device. For optimum control of this 25-level voltage inverter, a special Modified Hybrid Modulation technique is performed. The proposed 25-level inverter is compared to various topologies published recently in terms of cost, the number of active power switches, clamped diodes, flying capacitors, DC floating capacitors, and the number of DC voltage sources. This comparison clearly shows that the proposed topology is cost-effective, compact, and very efficient. The effectiveness and the good performance of the proposed multilevel power converter (with and without PWM control) are verified and checked by computational simulations.